THE DISCOURSE OF WOMEN IN THE FRIDAY SPEECHES - Sibel AYDIN (Fırat University, 2019)
This study aims to shed some light on some questions regarding the cooperation between the Religious Affairs (Diyanet) and as a secular country, the Republic of Turkey, particularly on gender issue. For this reason, the data came from between 2005 and 2015 Friday Speeches which are prepared by the Diyanet. Friday Speeches, which are an Islamic tradition, are given by imams regularly at the time of Friday noon prayer like every other predominantly Muslim country. As a result, the study shows that there are similarities between the speeches and the state approaches towards women issue. In the state, either the political policies or Diyanet via Friday Speeches support and reinforce these patriarchal view towards women.